Tides and tidal currents in Ensenada de la Paz lagoon, - José Gómez-Valdés; Francisco J. Sandoval (Geofísica Internacional, 1997)
Tides and tidal currents are observed in Ensenada de la Paz, a shallow coastal lagoon in Baja California Sur, Mexico. The amplitudes of two semidiurnal harmonics increase towards the head and there is a notably phase lag with respect to the mouth in the principal harmonics of surface tide. However, the amplitude of the fortnightly tide decreases toward the head. It is suggested that this behavior is caused by an approximate balance between surface pressure gradient and quadratic bot¬tom friction. The influence of both bottom friction and basin configuration on surface tide are examined with a linear hy¬drodynamic model. Currents fall into two groups: a tidally-driven inlet flow and an interior flow wherein nonlinearities ap¬pear to be important. The relative importance of nonlinear interactions on tidal velocities is analyzed with a simple model.